Solute Carrier Family 1 (SLC1A1) Contributes to Susceptibility and Psychopathology Symptoms of Schizophrenia in the Han Chinese Population - Li, Wenqiang; Su, Xi; Chen, Tengfei; Li, Zhen; Yang, Yongfeng; Zhang, Luwen; Liu, Qing; Shao, Minglong; Zhang, Yan; Ding, Minli; Lu, Yanli; Yu, Hongyan; et al. (Frontiers in Psychiatry, 2020)
Objective: Schizophrenia (SZ) is a common and complex psychiatric disorder that has a significant genetic component. The glutamate hypothesis describes one possible pathogenesis of SZ. The solute carrier family 1 gene (SLC1A1) is one of several genes thought to play a critical role in regulating the glutamatergic system and is strongly implicated in the pathophysiology of SZ. In this study, we identify polymorphisms of the SLC1A1 gene that may confer susceptibility to SZ in the Han Chinese population. Methods: We genotyped 36 single nucleotide polymorphisms (SNPs) using Illumina GoldenGate assays on a BeadStation 500G Genotyping System in 528 paranoid SZ patients and 528 healthy controls. Psychopathology was rated by the Positive and Negative Symptom Scale. Results: Significant associations were found in genotype and allele frequencies for SNPs rs10815017 and rs2026828 between SZ and healthy controls (p = 0.002, 0.030; 0.020, 0.005, respectively). There were significant associations in genotype frequency at rs6476875 and rs7024664, and allele frequency at rs3780412 and rs10974573 between SZ and healthy controls (p = 0.020, 0.021, 0.026, 0.047, respectively). Meanwhile, significant differences were found in genotype frequency at rs10815017, rs2026828, and rs3780411 in males (p = 0.015, 0.011, 0.040, respectively), and rs7021569 in females (p = 0.020) between cases and controls when subdivided by gender. Also, significant differences were found in allele frequency at rs2026828 and rs7021569 in males (p = 0.003, 0.045, respectively), and rs10974619 in females (p = 0.044). Significant associations were found in the frequencies of four haplotypes (AA, CA, AGA, and GG) between SZ and healthy controls (χ2 = 3.974, 7.433, 4.699, 4.526, p = 0.046, 0.006, 0.030, 0.033, respectively). There were significant associations between rs7032326 genotypes and PANSS total, positive symptoms, negative symptoms, and general psychopathology in SZ (p = 0.002, 0.011, 0.028, 0.008, respectively). Conclusion: The present study provides further evidence that SLC1A1 may be a susceptibility gene for SZ. The genetic variations of SLC1A1 may be associated with the pathogenesis of schizophrenia and affect psychopathology symptoms.